Combination of arbuscular mycorrhizal fungi and phosphate solubilizing bacteria on growth and production of Helianthus tuberosus under field condition - Nacoon, Sabaiporn; Jogloy, Sanun; Riddech, Nuntavun; Mongkolthanaruk, Wiyada; Ekprasert, Jindarat; Cooper, Julia; Boonlue, Sophon (Scientific reports, 2021)
In this work, the effects of co-inoculation between an arbuscular mycorrhizal fungus (AMF) and a phosphate solubilizing bacteria (PSB) to promote the growth and production of sunchoke under field condition were investigated during 2016 and 2017. Four treatments were set up as follows: plants without inoculation, with AMF inoculation, with PSB inoculation and with co-inoculation of PSB and AMF. The results showed the presence of PSB and AMF colonization at the harvest stage in both years. This suggested the survival of PSB and successful AMF colonization throughout the experiments. According to correlation analysis, PSB positively affected AMF spore density and colonization rate. Also, both AMF and PSB positively correlated with growth and production of sunchoke. Co-inoculation could enhance various plant parameters. However, better results in 2016 were found in co-inoculation treatment, while AMF inoculation performed the best in 2017. All of these results suggested that our AMF and PSB could effectively promote growth and production of sunchoke under field conditions. Such effects were varied due to different environmental conditions each year. Note that this is the first study showing successful co-inoculation of AMF and PSB for promoting growth and yield of sunchoke in the real cultivation fields.